The state of HIV awareness after three decades of intervention in Ethiopia: The case of the Borana pastoral community in Southern Ethiopia - Kaba, Migissa; Haile Mariam, Damen (The Ethiopian Journal of Health Development, 2016)
AbstractBackground: HIV continues to be the major public health challenge in Ethiopia. Despite positive developments in prevention efforts during the last three decades, the pandemic has continued to spread further expanding to remote pastoral communities.Objective: The objective of this study is to determine the current state of awareness on modes of prevention, transmission and ‘misconceptions’ about HIV among the Borana pastoralist community in Ethiopia.Methods: A cross-sectional survey of 502 households, 69 in-depth interviews and nine Focus Group Discussion sessions with 68 participants were carried out to generate data. STATA Version 10 was applied to analyze the survey data while MAXQDA 10 qualitative data analysis software was used to summarize and code qualitative data for further analysis and interpretation. Results: The survey data revealed that only 10% of the respondents identified all modes of HIV prevention. Logistic regression analysis showed that those over 41 years of age (AOR=O.4; 95% CI=0.2-0.9) and those who do not discuss about sex with their partners (AOR=0.6; 95% CI=0.4-0.9) had significantly low knowledge about the modes of HIV prevention. Eighty nine percent of the respondents mentioned at most two modes without significant variation by sex, place of residence and discussion about sex with partners. Eighty two percent of the respondents were found to consider shaking hands, living and eating with someone living with HIV, and buying food stuff from an HIV positive shop keeper as a way for HIV transmission. Logistic regression analysis showed that those who are living in Arero and Teltele Districts (AOR=0.4; 95% CI = 0.2-0.6) were found to have more ‘misconceptions’ about the modes of HIV transmission. Qualitative data underscored that knowledge about modes of HIV prevention, transmission and ‘misconceptions’ were widespread. Health extension workers, school teachers, youth AIDS club members and the radio were found to be key sources of HIV information. Yet, these sources other than radio are not trusted at community level since they are considered young learners themselves.Conclusion and recommendations: After three decades of HIV prevention intervention, the majority of people in Banora still manifest limited awareness on the modes of HIV transmission and prevention. This implies the threat under which the community live and the need for quick intervention. Results of this study will assist HIV/AIDS prevention and control programs to tailor their interventions according to local contexts. [Ethiop. J. Health Dev. 2012;26(1):9-15]